Penyajian Tambua Tansa D Palano’s Art Pada Upacara Pesta Perkawinan Di Lubuk Basung Kabupaten Agam - Andri Saputra; Syeilendra Syeilendra (SENDRATASIK UNP, 2020)
This study aims to describe the presentation of TambuaTansaD'palanos Art at a wedding party in LubukBasung, Agam Regency. This study belongs to a qualitative research using descriptive method. The object of this research was the TambuaTansa D palano's Art Group in LubukBasung, Agam Regency. The instrument of this research was the researcheritself and was assisted by supporting instruments such as stationery, laptops, and cellphones. The data were collected through observation, interview, and documentation. In the results of the study, the author concludes that the presentation of TambuaTansa D palano's art at a wedding party in LubukBasung, Agam Regency, is used as welcoming and accompaniment musicof the braid and groom on the way to the location where the wedding ceremony is held.The presentation of Tambua Tansa D Palano's Art is a kind of ensemble which presents several songs: Short Atam and Long Atam. Its form is presented in a performing art / stage in a circular formation.The presentation of Tambua Tansa D Palano's Art at a wedding party is an ensemble whose presentation is in the form of an opposite lined up and leading to each other. It is presented at the wedding location/ in front of the bridal house and on the highway as accompaniment music. The presentation of Tambuatansa D Palano's art at the wedding party is presented with tambua songs that have existedbefore. It is prepared carefully and usually performed around 10in the morning until the procession is over.